Real-world study of multiple naloxone administration for opioid overdose reversal among bystanders - Randa Abdelal; A. Raja Banerjee; Suzanne Carlberg-Racich; Neyla Darwaza; Diane Ito; Jessica Shoaff; Josh Epstein (BMC, 2022)
Abstract Background The increasing prevalence of highly potent, illicitly manufactured fentanyl and its analogues (IMF) in the USA is exacerbating the opioid epidemic which has worsened during the COVID-19 pandemic. Narcan® (naloxone HCl) Nasal Spray has been approved by the US Food and Drug Administration as a treatment for opioid-related overdoses. Due to the high potency of IMF, multiple naloxone administrations (MNA) may be needed per overdose event. It is essential to determine the patterns of naloxone use, including MNA, and preferences among bystanders who have used naloxone for opioid overdose reversal. Methods A cross-sectional web-based survey was administered to 125 adult US residents who administered 4 mg Narcan® Nasal Spray during an opioid overdose in the past year. The survey asked about the most recent overdose event, the use of Narcan® during the event and the associated withdrawal symptoms, and participant preferences regarding dosages of naloxone nasal spray. An open-ended voice survey was completed by 35 participants. Results Participants were mostly female (70%) and white (78%), while reported overdose events most frequently occurred in people who were males (54%) and white (86%). Most events (95%) were successfully reversed, with 78% using ≥ 2 doses and 30% using ≥ 3 doses of Narcan® Nasal Spray. Over 90% were worried that 1 Narcan® box may not be enough for a successful future reversal. Reported withdrawal symptoms were similar in overdose events where 1 versus ≥ 2 sprays were given. Eighty-six percent of participants reported more confidence in an 8 mg versus a 4 mg naloxone nasal spray and 77% reported a stronger preference for 8 mg over 4 mg. Conclusions MNA occurred in most overdose events, often involving more sprays than are provided in one Narcan® nasal spray box, and participants predominantly expressed having a stronger preference for and confidence in an 8 mg compared to a 4 mg nasal spray. This suggests the need and desire for a higher dose naloxone nasal spray formulation option. Given that bystanders may be the first to administer naloxone to someone experiencing an opioid overdose, ensuring access to an adequate naloxone supply is critical in addressing the opioid overdose epidemic.